THE RELATIONSHIP OF PARENTING STYLES AND CHILDREN'S HEIGHT IN BANDAR DUA STATE KINDERGARTEN, BANDAR DUA SUB-DISTRICT, PIDIE JAYA DISTRICT - Risna Fazlaini; Fitria (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Height is a crucial anthropometric parameter. Generally, height measurements can be used to calculate Body Mass Index (BMI). Individually, height measurements in children can be used to determine nutritional status, while height measurement data in a population can be used to assess growth standards. Determining the nutritional status of children, especially children under the age of five, is essential, considering that the incidence of malnutrition in this range of age can lead to disruption of the child's growth and development function, the impact of which will still be visible in adulthood. The role of mothers and parenting styles greatly influence the nutritional status of toddlers. Family parenting patterns influence the nutritional status of toddlers because toddlers still rely on their parents in fulfilling their food intake and health care. Meanwhile, the quality of food and nutrition depends on the family's parenting patterns. Analytical research design with a cross sectional study was conducted in Bandar Dua public kindergarten, Pidie Jaya Regency on 7-12 October 2022. This research used a sample of 58 mothers with a total sampling technique. The research instrument used a questionnaire and microtools. The research results: generally, the parenting style is permissive (55.2%), nutritional status was generally normal (79.3%), and a P value of 0.000 was obtained. Conclusion: there is a relationship between parenting styles and the height of kindergarten children. Parents should change their parenting style from authoritarian to democratic or permissive parenting.